The Predecessors of Bitcoin and Their Implications for the Prospect of Virtual Currencies - Kim, Thomas (PLOS ONE, 2015)
To examine whether the recent price patterns and transaction costs of Bitcoin represent a general characteristic of decentralized virtual currencies, we analyze virtual currencies in online games that have been voluntarily managed by individuals since 1990s. We find that matured game currencies have price stability similar to that of small size equities or gold, and their transaction costs are sometimes lower than real currencies. Assuming that virtual currencies with a longer history can provide an estimate for Bitcoin’s prospects, we project that Bitcoin will be less influenced by speculative trades and become a low cost alternative to real currencies.